The bean fly, Ophiomyia phaseoli (Tryon) (Diptera: Agromyzidae) - Gonzáles V., F.; Menendez F., L. (1986)
A vast literature review is given on the bean fly (Ophiomyia phaseoli). Aspects dealt with are geographical distribution, host plants, biology, plant damage, and pest management (cultural, biological, and chemical control, and var. resistance). The importance of an integrated pest management is highlighted, based on the correct identification of the pest and a profound knowledge of its biology and the factors regulating its population. (CIAT)